PERSPEKTIF MAHASISWA BARU TENTANG CHAT GPT - Hasani, Zhul Fahmy; Lestiyanawati, Rochyani; Adi, Nugroho Prasetya (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2024)
Great developments in technology make it easier for humans to access various information very quickly, one of which is the use of GPT chat to make it easier for humans to do their work. Data collection in this research was carried out by distributing questionnaires online to students regarding GPT chat using the survey method. Based on the research results, it can be synthesized that new students already understand what GPT chat is. This shows that GPT chat is no longer foreign to students, because of the impact of increasingly rapid technological developments. Apart from that, most students have used GPT chat to complete assignments given by lecturers. The majority of students stated that GPT chat is very useful for students, this is a big alarm for educators considering that if students always use GPT chat to help with their lecture process, it can have a negative impact, one of which is a decrease in students' critical and analytical skills. The positive impact that arises from using GPT chat is that students gain new knowledge that can be used to help develop soft skills.